The Thinker of the Future: Мислителот на иднината - Cornell, Drucilla; Stoev, Goran (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Drucilla Cornell | Друсила Корнел Title (English): The Thinker of the Future Title (Macedonian): Мислителот на иднината Translated by (English to Macedonian): Goran Stoev | Горан Стоев Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 27-32 Page Count: 6 Citation (English): Drucilla Cornell, “The Thinker of the Future,” Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004): 27-32. Citation (Macedonian): Друсила Корнел, „Мислителот на иднината“, превод од англиски Горан Стоев, Идентитети: списание за политика, род и култура, т. 3, бр. 2 (зима 2004): 27-32.